Courageous Resistance - Thalhammer, K. author. aut Link
XI, 210 p.
Keywords: During times of injustice, some individuals or groups courageously resist maltreatment of all people, regardless of backgrounds. Using various case studies, this book introduces readers to the broad spectrum of courageous resistance and provides a framework for analyzing the factors that motivate and sustain opposition to human rights violations.